Communication: From the Internet to the Intelligent - Zheng, Xiaomei; Wang, Lingfeng (Journal of Intelligent Communication, 2022)
According to contemporary history of new technologies, today’s Internet age is inevitably going to the terminal point of its first half, and then the Internet of Things has been formed in this stage. Following the Internet and the Internet of Things, the Internet of People is coming. In the new stage, the intelligent communication will still keep the previous concern about fresh information and network technologies along with their influences on the one side, and on the other side it will focus on the connection between human and intelligent technologies. This brings three dimensions taken into consideration. The primary issue is the way that intelligent technologies reshape the forms of communication and media, and the relations among technologies, media, the public and societies. The development trends and rules of communication and media forms correlate with the latest and also the future information technologies, such as big data, VR, AR, MR, AI and machine learning, 5G and 6G, wearable devices, and some unknown new stuff. In the future, intelligent technologies will probably have a broad and profound influence on the production and consumption of journalism. So far many media organizations have taken advantages of 5G and AI in creating better journalism at a time, just like what they did during the Tokyo Olympics. They can also help the public work with overload information and access to credible content globally in a more convenient way. Furtherly, 6G. and metaverse will introduce completely new communication paradigms by building developer-friendly tools and practicing their disruptive concepts. And With smart data, smart media can simplify and enrich human activities and experiences. In the world of the Internet of People based on these technologies, human-machine interaction sight system will gain a benefit of higher immersion and more imaginations but lower interference and permeability. The impact of this virtual media world is uncertain but is surely accelerating the transformation towards more diverse societies and independent digital identities.